CTL Model; Arabic Language Learn The Application Of The Contextual Teaching And Learning (CTL) Model In Arabic Language Learning To Improve The Learning Outcomes - Ibnu Haryono; Khizanatul Hikmah (Buana Pendidikan, 2023)
This study aims to describe the improvement of learning outcomes through the Contextual Teaching and Learning model in learning Arabic. This type of research is quantitative descriptive research, conducted by conducting classroom action with two cycles of action. The results of this study indicate that the application of the Contextual Teaching and Learning (CTL) model can improve oral and written language skills. Student learning outcomes in the initial conditions of Arabic learning outcomes are lower, with an average value of 66,2. After taking action by applying the Contextual Teaching And Learning (CTL) learning model, the results of learning Arabic have improved, namely in the first cycle with an average value of 73, and after being given treatment in the second cycle, the Arabic learning outcomes are very good with an average value of 83, above the average score. Thus, the application of the Contextual Teaching and Learning (CTL) learning model can improve oral and written language skills in each cycle.